A eugenia no humor da Revista Ilustrada Careta: raça e cor no Governo Provisório (1930-1934) - Carvalho, Leonardo Dallacqua [UNESP] (2014)
With the beginning of the interim goverment in 1930, Brazil enters a new political Era under the government of Getúlio Vargas. Besides his break with the past government, his period would be marked by innovative proposals in different social areas, as for instance, work rights, functionalist, educational, economic, between others. Moreover, he had some particular political characteristics in relation to migrants, communists, jews, blacks, etc. The debates that sparked between the intelligentsia, political sphere and press permitted that questions in relation to color and race had their reserved space for discussions and actions between 1930 and 1934. For us, in relation to this discussion, we analyzed the role of eugenics in this process. Through the weekly magazine Careta, printed in Brazil since 1908, we have an important source of data that combines humor with social critic to analyze. In the first years of the Era Vargas, the weekly magazine, in numerous editions considered through cartoons and cronics the color and race situations in relation to the wider social organism in Brazil. Our work has as an objective to analyze the weekly magazine and problematize the magazine's humoristic approach to the racial question within society, as well as about eugenics in Brazil